Extended nitric oxide-releasing polyurethanes via S-nitrosothiol-modified mesoporous silica nanoparticles - Malone-Povolny, Maggie J. (ACS Appl Mater Interfaces, 2019)
S-nitrosothiol (RSNO)-modified mesoporous silica nanoparticles (MSNs) were doped into polyurethane (PU) to achieve extended NO-releasing coatings. Parameters influencing the synthesis of RSNO-functionalized nitric oxide (NO)-releasing MSNs were evaluated to elucidate the impact of pore structure on NO-release characteristics. The porous particles were characterized as having larger NO payloads and longer NO-release durations than that of nonporous particles, a feature attributed to recombination of the NO radical in confined intraporous microenvironments. Nitric oxide-release kinetics, particle leaching, and thermal stability of the RSNO-modified MSNs dispersed in PU were evaluated as a function of PU structure to determine the feasibility of preparing a range of NO-releasing polymers for biomedical device coating applications. The NO-release kinetics from the PUs proved to be highly extended (>30 d) and consistent over a range of polyurethane properties. Furthermore, RSNO-modified MSN leaching was not observed from the PUs. The NO-release payloads were also maintained for 4 days for polymers stored at 0 °C.